Une flamme si noir: Historier om rationalitet fortalt i to Fædra-tekster. - Szatkowski, Janek (Peripeti, 2021)
Janek Szatkowski methodically examines the relationship between Euripides’ Hippolytos and Racine’s Phèdre, and unearths a significant difference in the principle of rationality that governs the works.